2010
DOI: 10.1002/joc.2214
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal temperature trends on the Yunnan Plateau (Southwest China) during 1961–2004

Abstract: Monthly mean (TEM), maximum (T max ) and minimum (T min ) surface air temperatures at 119 meteorological stations on the Yunnan Plateau (YP, Southwest China) were analysed for temporal trends and spatial variation patterns during the period 1961-2004. Linear trend analyses revealed that annual temperature over the YP increased at a rate of 0.3°C/decade during the period 1961-2004, while warming trend of 0.33°C/decade and 0.26°C/decade was observed for winter and summer temperatures, respectively. Warming trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 59 publications
9
72
2
Order By: Relevance
“…The annual temperature also reports an increasing tendency; however, there are distinct differences in the trend for minimum temperature and maximum temperature (minimum temperature increased more rapidly). Our result is in good agreement with Fan et al [15], who reported a higher increase in minimum temperature than maximum temperature in southwest China. The overall warming rate in the dry and terrace regions exceeds the global mean of 0.14 °C per decade (0.31 and 0.25 °C, respectively) [5].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The annual temperature also reports an increasing tendency; however, there are distinct differences in the trend for minimum temperature and maximum temperature (minimum temperature increased more rapidly). Our result is in good agreement with Fan et al [15], who reported a higher increase in minimum temperature than maximum temperature in southwest China. The overall warming rate in the dry and terrace regions exceeds the global mean of 0.14 °C per decade (0.31 and 0.25 °C, respectively) [5].…”
Section: Discussionsupporting
confidence: 94%
“…Often only densely homogeneous historical-or global-scale datasets are available [20], while few assessments exist at a national level [4,16]. It is important to conduct studies at a smaller scale due to the large regional differences in surface temperature [15,20] and rainfall [37]. The IPCC [21] report highlights the need for more detailed information about climate change at regional and local scales.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Some prior studies using observational data have shown positive correlations of the elevation with the warming rate in the European Alps (Beniston and Rebetez 1996), Nepal Himalayas (Shrestha et al 1999), Yunnan Plateau in China (Fan et al 2011), and the Tibet Plateau (Liu and Chen 2000). The warming is more pronounced at higher elevations in those areas.…”
Section: Elevation Dependence Of the Near-surface Air Temperature mentioning
confidence: 89%
“…The warming trend in high-altitude areas, such as the Tibetan Plateau and its south-east margin, has been observed to be more pronounced (Fan et al, 2011;Liu and Chen, 2000). Several studies of CO 2 exchange have been carried out on the Qinghai-Tibetan plateau, where the mean annual air temperature (T a ) is approximately 0 • C (Gu et al, 2003;Kato et al, 2006;Shi et al, 2006;Zhao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%